Línguas de fogo em berços d'água: a tragédia do navio cargueiro Maria Celeste em disputa - Azoubel, Diogo (2021)
This research investigates the nature of the photojournalistic coverage of the fire and successive explosions of the cargo ship Maria Celeste, off the coast of Maranhão, Brazil, from March 16, 1954. Articulated in nine interdependent reflections, the discussion takes place through the literature review as a route to qualiquantitative analysis. Printed periodicals produced and circulated during the second half of that month in São Luís are the empirical object, with a record of the pages of newsprint that, in some way, narrate the verbal-visual- spatial event between the 16th and the 31st. The epistemological look congregates concepts from related areas, such as Art, Social Sciences, Photography, History, and Journalism from semiotics as the founding axis. The results achieved point to a sensitive disqualification of the victims of the action of fire over water in the journalistic narrative, as well as the silencing of the public powers about the tragedy